Enteral nutrition before bowel preparation improves the safety of colonoscopy in the elderly - Jianfeng YAO,; Wei ZHANG,; Jie CHEN,; Gansheng ZHANG,; Songbai ZHENG, (Turkish Journal of Gastroenterology, 2019)
-